PELATIHAN SECARA DARING PEMANFAATN MENDELEY SEBAGAI SOFTWARE MANAJEMEN REFERENSI DARI KARYA ILMIAH - Siti Qomariah; Andi Yusika Rangan; Eka Arriyanti (LPPM UNIKS, 2022)
The Covid-19 pandemic does not prevent it from continuing to improve self-knowledge and competence. But the way it is done is no longer offline or face-to-face to be present in an activity or class but is carried out online. One of the improvements in self-competence that students must have is the ability to manage citations and reference articles from various scientific journals. one of the citation software that can be cloud-based and also desktop-based is mendeley. the activities carried out are open to the public in the framework of community development programs with the aim of increasing the ability to write scientific papers. Activities are carried out by lecture and practice methods, for the delivery of material is carried out by the lecture method, yes answer, demostration or practice. while to find out the success of an activity, a surver is carried out in the form of pretests and post tests. All activities are carried out online using zoom and google forms. from the results of the pre-test and post-test, there was an increase in the ability of trainees from 43.8% to 74.54%The Covid-19 pandemic does not prevent it from continuing to improve self-knowledge and competence. But the way it is done is no longer offline or face-to-face to be present in an activity or class but is carried out online. One of the improvements in self-competence that students must have is the ability to manage citations and reference articles from various scientific journals. one of the citation software that can be cloud-based and also desktop-based is mendeley. the activities carried out are open to the public in the framework of community development programs with the aim of increasing the ability to write scientific papers. Activities are carried out by lecture and practice methods, for the delivery of material is carried out by the lecture method, yes answer, demostration or practice. while to find out the success of an activity, a surver is carried out in the form of pretests and post tests. All activities are carried out online using zoom and google forms. from the results of the pre-test and post-test, there was an increase in the ability of trainees from 43.8% to 74.54%